Extended High Frequency Hearing Thresholds in Tinnitus Patients with Normal Hearing - RISTOVSKA, Lidija; JACHOVA, Zora (Archives of Acoustics, 2022)
The aim of the study was to compare the extended high-frequency (EHF) hearing thresholds (10–16 kHz) in tinnitus and non-tinnitus ears, in a group of 98 patients with unilateral tinnitus and normal hearing at standard audiometric frequencies, in a 0.125–8 kHz range. It was found that a total of 65 patients (66%) had a hearing loss (a threshold shift >20 dB HL) in the EHF range and the EHF hearing loss occurred more frequently in the tinnitus ear than in the non-tinnitus ear. The data also indicate that the EHF thresholds increased with the patient’s age and were in most patients higher in the tinnitus ear than in the non-tinnitus ear.